The creation of Itaipu Lake as a river territory of practices and discourses of canonical and deviant leisure (PerCursos, 2023)
The purpose of this article is to analyze how the construction of Usina Binacional de Itaipu produced practices and discourses able to constitute deviant leisure activities. The limitation of territory use resulted in the use of leisure as a apparatus by different agents. The removal of the dwelling place, the sensation of loss of freedom to access to the river, the transformation of the fluvial region into a tourist and market center, the desire to venture and satisfaction for transgression can be read as factors leading to deviant leisure.
Keywords: leisure; apparatus; territory